2022
DOI: 10.3390/app12105179
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Flow Field and Aerodynamic Load on Impellers under Guide Vanes with a Self-Induced Slot in Compressor Radial Inlet

Abstract: The flow field and the efficiency of the compressor can be improved and increased by the guide vane in the radial inlet chamber. However, the guide vane generates the wake and results in the rotor–stator interaction, which threatens the safety of the impeller. This paper investigated the guide vane with a self-induced slot (SIS) in a radial inlet, and the self-induced slot was a passive flow control method. Through computational fluid dynamics (CFD) simulation, the radial inlet containing unevenly distributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A numerical simulation of multihole impingement cooling of a turbine guide vane cavity [12] with a complex pin fin structure was conducted. Xin et al [13] carried out a numerical simulation of a radial intake chamber with guide vanes with self-guide grooves. Guide vanes could improve and enhance the flow and efficiency of the airflow within the compressor.…”
Section: Computational Modelmentioning
confidence: 99%
“…A numerical simulation of multihole impingement cooling of a turbine guide vane cavity [12] with a complex pin fin structure was conducted. Xin et al [13] carried out a numerical simulation of a radial intake chamber with guide vanes with self-guide grooves. Guide vanes could improve and enhance the flow and efficiency of the airflow within the compressor.…”
Section: Computational Modelmentioning
confidence: 99%
“…Grimaldi [10] experimentally tested the overall performance of compressor units with different RIC models and found that there needed to be a balance between the complexity of the RIC structure and the impact on first-stage performance. Xin [11] numerically calculated compressor with uneven guide vanes and the results show that the guide vanes wake and the pressure load threaten the impeller safe operation. Pazzi [12] tested the performance of a typical RIC through numerical simulation and experiment, and found that the number and structure of shunt blades in the RIC have a great influence on the flow field, mainly because it can change the distribution of aerodynamic parameters in the tangential direction.…”
Section: Introductionmentioning
confidence: 99%